FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA MANAJEMEN RISIKO PASOKAN DALAM RITEL BUKU DAN ALAT TULIS DI SURABAYA - Mella Carissa Gunawan; Fitri Novika Widjaja; Stefanus Budy Widjaja S. (Perpustakaan Universitas Surabaya, 2018)
This study aims to analyze factors which influence risk management performance. Variables which are used, supplier orientation, supplier dependency, customer orientation, and systemic purchasing toward the risk management performance in retail book and stationary at Surabaya. This research uses quantitative approach by using multiple linear regression. The sample of the study is the retail book and stationary at Surabaya. The total sample is 91. Research finding indicates that supplier orientation and supplier dependency give significantly positive effect to risk management performance. While customer orientation and systemic purchasing aren’t significant yet they give positive effect to risk management performance.